The Authority of Local Governments in Land Arrangement and Management Perspective of Maslahah Theory - Musleh Harry; Imam Sukadi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this research is to find out and analyze the rationale of local government in conducting land management and management and to know and analyze the authority of the Regional Government in structuring and managing the perspective of Maslahah's theory. The rationale for the authority of the regional government to arrange and manage land comes from Article 12 paragraph (2) letter d of Law No. 23 of 2014 concerning Regional Government, because the essence of regional autonomy is to bring services closer to the community. The authority of the regional government in structuring and managing the land of the perspective of the maslahah theory includes the Hajjiyah maslahah, the benefit needed by the community to perfect the basic benefit or something needed by humans, but has not yet reached the level of dharuri.